Can the Argentine ant (Linepithema humile Mayr) replace native ants in myrmecochory? - Gómez, Crisanto; Oliveras, Jordi (Acta Oecologica, 2003)
We analyse the inﬂuence of the Argentine ant (Linepithema humile Mayr) on the seed dispersal process of the myrmecochorous plants Euphorbia characias, E. biumbellata, Genista linifolia, G. triﬂora, G. monspessulana and Sarothamnus arboreus. The observations were made in two study plots of Mediterranean cork-oak secondary forest (invaded and non-invaded by L. humile). The presence of L. humile implies the displacement of all native ant species that disperse seeds. Seed transports in the non-invaded zone were carried out by eight ant species. In the invaded zone, L. humile workers removed and transported seeds to the nest. In vertebrate exclusion trials, we observed the same level of seed removal in the invaded and non-invaded zones. Two ﬁndings could explain this result. Although mean time to seed localization was higher for native ants (431.7 s) than that for L. humile (150.5 s), the mean proportion of seeds transported after being detected was higher (50.1%) in non-invaded than in invaded (16.8%) zones. The proportion of seeds removed and transported into an ant nest after an ant-seed interaction had dramatically reduced from non-invaded (41.9%) to invaded (7.4%) zones. The levels of seed dispersal by ants found prior to invasion are unlikely to be maintained in invaded zones. However, total replacement of seed dispersal function is possible if contact iteration ﬁnally offers similar levels or quantities of seeds reaching the nests. The results obtained conﬁrm that the Argentine ant invasion may affect myrmecochory dramatically in the Mediterranean biome.
Keywords: ant-plant mutualism; Argentine ant; Biological invasion; Linepithema humile; myrmecochory; seed dispersal